Accuracy in detecting and measuring residual fragments with the Uro Dyna-CT - Meister, Benjamin; Rassweiler-Seyfried, Marie-Claire; Weiß, Christel; Häcker, Axel; Ritter, Manuel (World journal of urology, 2014)
Background and purpose: Residual calculi after stone therapy need to be treated if they are clinically significant, mainly depending on the size of the calculi. There are different ways to detect and measure the size of residual calculi as for example KUB or computed tomography. The Uro Dyna-CT (Siemens Healthcare solutions, Erlangen, Germany) allows cross-sectional imaging and 3D reconstructions during endourological interventions. In this ex vivo study, we investigate the accuracy of imaging residual calculi with the Uro Dyna-CT. Materials and methods: Twenty-seven artificial stones (plaster of Paris) were scanned with the Uro Dyna-CT by a special urolithiasis protocol and post-image processing with 3D-reconstruction and cross-sectional imaging was performed. The major diameter of each stone was measured at the dedicated workstation by one investigator. The same stones were measured randomized with a digital caliper (real size). Finally, the two measurements were compared. The paired t test, Pearson’s correlation coefficient, the F Test, a reference area for differences, the intraclass correlation coefficient, the Maloney-Rastogi test and the Bland-Altman analysis were used for statistical analyses. Results: The range of stone sizes was 3-5 mm. We did not find significant differences in the size of the stones measured with the Uro Dyna-CT and the digital caliper (paired t test p = 0.3597) and we showed a good correlation between the two measuring methods (intraclass correlation coefficient 0.4465; p = 0.0088). Conclusion: Renal calculi can be measured highly accurately with the Uro Dyna-CT. Whether this technique will lead to less residual fragments after stone treatment needs to be shown in further studies.